THE CONCEPT OF "ARTISTIC FORM" AND ITS ESSENCE AND CLASSIFICATION IN UZBEK POETRY OF THE INDEPENDENCE YEARS - Tashova Dilorom Salimovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article discusses the formal and stylistic research in Uzbek literature of the period of independence, their artistic and aesthetic factors, the important features of poetry being updated under the influence of Uzbek classical literature and world poetry. The difference between a literary genre and an artistic form is shown with the help of a number of scientific sources and evidence. In recent years, the works of artists who have conducted artistic research in Uzbek literature and their unique aspects will be discussed.